Ion microprobe assessment of the heterogeneity of Mg/Ca, Sr/Ca and Mn/Ca ratios in Pecten maximus and Mytilus edulis (bivalvia) shell calcite precipitated at constant temperature. - Clarke, Leon J. (2011)
no === Small-scale heterogeneity of biogenic carbonate elemental composition can be a significant source of error in the accurate use of element/Ca ratios as geochemical proxies. In this study ion microprobe (SIMS) profiles showed significant small-scale variability of Mg/Ca, Sr/Ca and Mn/Ca ratios in new shell calcite of the marine bivalves Pecten maximus and Mytilus edulis that was precipitated during a constant-temperature culturing experiment. Elevated Mg/Ca, Sr/Ca and Mn/Ca ratios were found to be associated with the deposition of elaborate shell features, i.e. a shell surface stria in P. maximus and surface shell disturbance marks in both species, the latter a common occurrence in bivalve shells. In both species the observed small-scale elemental heterogeneity most likely was not controlled by variable transport of ions to the extra-pallial fluid, but by factors such as the influence of shell organic content and/or crystal size and orientation, the latter reflecting conditions at the shell crystalsolution interface. In the mid and innermost regions of the P. maximus shell the lack of significant small-scale variation of Mg/Ca ratios, which is consistent with growth at constant temperature, suggest a potential application as a palaeotemperature proxy. Cross-growth band element/Ca ratio profiles in the interior of bivalve shells may provide more promising palaeo-environmental tools than sampling from the outer region of bivalve shells.